A polytetrafluoroethylene membrane with gradient pore structure and preparation method thereof

Through the preparation of the polytetrafluoroethylene membrane with gradient pore structure, the problem that existing porous PTFE membranes are difficult to maintain high filtration accuracy and mechanical strength when improving the filtration rate and permeability is solved, and the comprehensive effect of low resistance, high flow rate and high filtration accuracy is achieved.

CN117861465BActive Publication Date: 2025-03-07FEATURE TEC (SHANGHAI) ADVANCED MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211631082.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-03-07
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

When the existing porous PTFE membranes improve the filtration rate and permeability, it is difficult to maintain high filtration accuracy and mechanical strength, and the preparation process is complicated, which easily leads to damage to the membrane material.

Method used

A polytetrafluoroethylene film having a gradient pore structure is prepared by mixing, extruding, laminating and stretching isomeric alkanes and PTFE dispersing resin, forming a gradient pore structure of the first porous outer surface and the second porous outer surface.

Benefits of technology

It achieves the characteristics of low resistance and high flow rate without reducing thickness and filtration accuracy, improves filtration efficiency and ability to capture pollutants, and reduces energy cost and system space.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117861465B_ABST
    Figure CN117861465B_ABST
Patent Text Reader

Abstract

The present invention provides a polytetrafluoroethylene membrane with a gradient pore structure and a preparation method thereof. The cross section of the membrane has a gradient pore structure. The first porous outer surface and the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane have fibers and nodes with different microstructures; the first porous outer surface has an island-like microstructure constructed by a plurality of interconnected smaller nodes, and the second porous outer surface has an H-shaped ladder-like microstructure constructed by a plurality of interconnected larger nodes. The PTFE membrane material with a gradient pore structure prepared by the method has the characteristics of low resistance and high flow rate without reducing the thickness and filtering accuracy, and the improvement of filtering efficiency enhances the capture of pollutants. For a given transmembrane pressure drop, the high permeability or high flow capacity of the membrane reduces the resistance loss, shortens the filtration time, and thus reduces the energy cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer filtration membrane materials, in particular to a polytetrafluoroethylene membrane with a gradient pore structure and a preparation method thereof. Background Art

[0002] Expanded polytetrafluoroethylene (hereinafter referred to as PTFE) membranes with porous structures have been widely used in the field of liquid and gas filtration. This type of membrane has high chemical inertness and thermal stability at extreme temperatures and can be used under very harsh working conditions.

[0003] As mentioned in US Pat. No. 3,953,566A, PTFE resin and lubricant are mixed to form raw materials, the PTFE mixed raw materials are formed into blanks and then paste is extruded, and after the lubricant is removed from the extruded material, the PTFE product is stretched to produce a porous PTFE product. The expanded PTFE material is characterized by having a porous microstructure with nodes connected by fibrils, and the pore size inside and on both surfaces of the membrane is relatively uniform, which is a symmetrical pore structure.

[0004] Symmetrical pore structure filter materials can have high filtration accuracy. The smaller the pore size, the more accurate the filtration or separation. However, the smaller pore size usually reduces the permeability of liquid or gas through the membrane and cannot provide a high dirt holding capacity. On the contrary, if the flow capacity of the membrane is increased by increasing the pore size of the filter material, but this results in a decrease in the particles captured by the membrane, the filtration efficiency will decrease.

[0005] In order to increase the processing volume per unit area and per unit time and improve the filtration rate, the number of holes must be greatly increased or the thickness of the membrane material must be minimized while ensuring a certain pore size. Under specific production conditions, it is very difficult to significantly increase the number of pores per unit area. In addition, although the filtration rate can be increased by reducing the thickness of the filter material, it will lead to a weakening of the mechanical strength of the film. The focus of developing filter materials is to find an ideal combination of high permeability and high filtration accuracy, while ensuring filtration efficiency, having low resistance, high flow rate and high pollution holding capacity. As a technology to overcome this defect, asymmetric porous membranes have greater processing capacity under the same filtration or separation conditions.

[0006] Although the filtration properties of porous PTFE membranes are constantly improving, PTFE filtration membranes that can simultaneously provide small particle size and low flow resistance remain one of the technical difficulties in this field.

[0007] The filter material with asymmetric pore structure can ensure high filtering accuracy while having the advantages of small pressure difference and long service life, and is widely used in the field of filtration and separation. For example, Chinese patent CN107810047A discloses an asymmetric polytetrafluoroethylene composite with a macro-textured surface, and the two membrane surfaces of the polytetrafluoroethylene composite have different bubble point pressure values. In this method, the second PTFE membrane needs to expand the rolled strip in the longitudinal or transverse direction when the lubricant is not removed while it is wet. This operation is difficult to implement and is easy to cause irreversible damage to the PTFE strip. Although the membrane prepared by this method has a unique macro-textured surface, there are one or more strands on the membrane surface and they are raised from the membrane surface, which may cause uneven stress between layers when compounded with other supporting layers.

[0008] For example, US Pat. No. 4,248,924A provides a porous film material composed of polytetrafluoroethylene with an asymmetric structure, which is prepared by stretching the film using a pair of rotating rollers with a temperature difference of 50°C or higher. The temperature gradient in the thickness direction generated by the temperature difference between the front and back surfaces of the film and the combination of the compression force in the thickness direction produce an asymmetric structure in the obtained porous film material, characterized in that the fiber structure in the front surface is different from the fiber structure in the back surface. Often, due to the thin thickness of the stretched film, the temperature gradient generated in the thickness direction by this method is limited, and the asymmetric structure in the film material cannot be well controlled.

[0009] In view of this, it is necessary to improve the asymmetric membrane materials and preparation methods thereof in the prior art to solve the above problems. Summary of the invention

[0010] The purpose of the present invention is to disclose a polytetrafluoroethylene membrane material with a gradient pore structure, which combines the characteristics of low flow resistance and small pore size, so that it has excellent filtration rate and reliable retention accuracy in liquid and gas filtration.

[0011] To achieve the above-mentioned purpose, the present invention provides a polytetrafluoroethylene membrane with a gradient pore structure, wherein the cross-section of the polytetrafluoroethylene membrane has a gradient pore structure, and the first porous outer surface and the second porous outer surface of the polytetrafluoroethylene membrane have fibers and nodes with different microstructures; the first porous outer surface has an island-like microstructure constructed by a plurality of interconnected smaller nodes, and the second porous outer surface has an H-shaped ladder-like microstructure constructed by a plurality of interconnected larger nodes.

[0012] In some embodiments, the smaller nodes are round structures with an average diameter of 0.30 to 1.50 μm.

[0013] In some embodiments, the smaller nodes are formed by connecting a plurality of thick and short microfibers, the average length of the thick and short microfibers is in the range of 0.2 to 2.5 μm, the average diameter is in the range of 0.05 to 0.2 μm, and the aspect ratio is 2 to 20.

[0014] In some embodiments, the larger nodes are oblong structures with an average length of 0.5 to 10 μm and an average width of 0.5 to 2 μm.

[0015] In some embodiments, the larger node is formed by connecting a plurality of elongated microfibers, wherein the elongated microfibers have an average length ranging from 1 to 10 μm, an average diameter ranging from 5 to 200 nm, and an aspect ratio of 10 to 200.

[0016] Another object of the present invention is to provide a method for preparing a PTFE porous membrane with a gradient pore structure, comprising the following steps:

[0017] (1) First, isoparaffin and PTFE dispersed resin are uniformly mixed to obtain a PTFE resin mixture, and then the PTFE resin mixture is pressed into a cylindrical preform;

[0018] (2) using an extruder to extrude the cylindrical preform into three continuous strips of equal width and different thicknesses with rectangular cross-sections through T-shaped extrusion dies of different specifications, namely, a first sheet, a second sheet, and a third sheet;

[0019] (3) The first sheet, the second sheet, and the third sheet are stacked in the same width direction in increasing or decreasing thickness, and are fed into a pair of metal rollers in the length direction and rolled in the thickness direction to a range of 0.05 to 1 mm to form a laminate;

[0020] (4) drying the laminate at 200 to 250° C., and then expanding the laminate in a speed direction at 250 to 350° C. at a stretching rate of 20% / s to 3000% / s and an expansion ratio of 50% to 900% to form a uniaxially stretched product;

[0021] (5) Expanding the uniaxially stretched product in a direction perpendicular to the speed at a temperature of 200 to 400° C., at a stretching rate of 5% / s to 500% / s, and at a ratio of 300% to 3000%, to finally form a PTFE membrane material with a gradient pore structure.

[0022] In some embodiments, in step (1), isoparaffin and PTFE dispersed resin are uniformly mixed in a weight ratio of 15 to 30% to obtain a PTFE resin mixture, and the mixture is dried at a temperature not less than 20° C. for more than 12 hours, and the PTFE resin mixture is pressed into a cylindrical preform.

[0023] In some embodiments, in step (2), the cylindrical preform is extruded into three continuous strips of equal width with different thicknesses and rectangular cross-sections through T-shaped extrusion dies of different specifications at a compression ratio of 20 to 500, which are respectively a first sheet, a second sheet and a third sheet, wherein: the thickness of the second sheet is at least 1.2 times the thickness of the first sheet, the thickness of the third sheet is at least 1.2 times the thickness of the second sheet, and the compression ratio of the first sheet is at least 2.5 times that of the second sheet and 3 times that of the third sheet.

[0024] In some embodiments, in step (4), the laminate is expanded along the speed direction at a stretching rate of 50% / sec to 2000% / sec and an expansion ratio of 80% to 800% to form a uniaxially stretched product.

[0025] In some embodiments, in step (5), the PTFE membrane material having a gradient pore structure is finally formed by expanding in a direction perpendicular to the speed at a stretching rate of 20% / sec to 300% / sec and a ratio of 500% to 2500%.

[0026] Compared with the prior art, the present invention has the following beneficial effects: the polytetrafluoroethylene membrane material with gradient pore structure prepared by the method has the characteristics of low resistance and high flow rate without reducing thickness and filtration accuracy, and the improvement of filtration efficiency enhances the capture of pollutants. For a given transmembrane pressure drop, the high permeability or high flow capacity through the membrane reduces resistance loss, shortens filtration time, and thus reduces energy costs. In addition, these characteristics can provide a system with smaller installation space and more cost-saving. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a cross-sectional view of a polytetrafluoroethylene film stack according to the present invention;

[0028] Figure 2 This is a 2000-fold scanning electron micrograph of the first porous outer surface of the polytetrafluoroethylene membrane shown in Example 1 of the present invention;

[0029] Figure 3 This is a 2000-fold scanning electron micrograph of the second porous outer surface of the polytetrafluoroethylene membrane shown in Example 1 of the present invention;

[0030] Figure 4 This is a 2000-fold scanning electron micrograph of the first porous outer surface of the polytetrafluoroethylene membrane shown in Example 2 of the present invention;

[0031] Figure 5 This is a 2000-fold scanning electron micrograph of the second porous outer surface of the polytetrafluoroethylene membrane shown in Example 2 of the present invention;

[0032] Figure 6This is a 2000-fold scanning electron micrograph of the first porous outer surface of the polytetrafluoroethylene membrane shown in Example 3 of the present invention;

[0033] Figure 7 This is a 2000-fold scanning electron micrograph of the second porous outer surface of the polytetrafluoroethylene membrane shown in Example 3 of the present invention;

[0034] Figure 8 This is a 2000-fold scanning electron micrograph of the first porous outer surface of the polytetrafluoroethylene membrane shown in Example 4 of the present invention;

[0035] Fig. 9 This is a 2000-fold scanning electron micrograph of the second porous outer surface of the polytetrafluoroethylene membrane shown in Example 4 of the present invention;

[0036] Fig.10 This is a 2000-fold scanning electron micrograph of the first porous outer surface of the polytetrafluoroethylene membrane shown in Example 5 of the present invention;

[0037] Fig.11 This is a 2000-fold scanning electron micrograph of the second porous outer surface of the polytetrafluoroethylene membrane shown in Example 5 of the present invention;

[0038] Fig.12 This is a 2000-fold scanning electron micrograph of the first porous outer surface of the polytetrafluoroethylene membrane shown in Example 6 of the present invention;

[0039] Fig.13 This is a 2000-fold scanning electron micrograph of the second porous outer surface of the polytetrafluoroethylene membrane shown in Example 6 of the present invention. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with the various embodiments shown in the accompanying drawings, but it should be noted that these embodiments are not limitations of the present invention, and any equivalent transformations or substitutions in functions, methods, or structures made by ordinary technicians in the field based on these embodiments are all within the scope of protection of the present invention.

[0041] The method for preparing a polytetrafluoroethylene membrane having a gradient pore structure of the present invention comprises the following specific steps:

[0042] (1) First, an isoparaffin lubricant and a polytetrafluoroethylene (PTFE) dispersed resin are uniformly mixed in a weight ratio of 15 to 30% to obtain a PTFE resin mixture, and the mixture is dried at a temperature not less than 20° C. for more than 12 hours, and the PTFE resin mixture is pressed into a cylindrical preform.

[0043] (2) Using an extruder, at a compression ratio of 20 to 500, preferably 30 to 250, the cylindrical preform is extruded through T-type extrusion dies of different specifications into three kinds of equal-width continuous strip sheets of different thicknesses with rectangular cross-sections, namely, the first sheet, the second sheet, and the third sheet.

[0044] Among them: the thickness of the second sheet is at least 1.2 times the thickness of the first sheet, preferably 1.2 to 5 times; the thickness of the third sheet is at least 1.2 times the thickness of the second sheet, preferably 1.2 to 5 times; the compression ratio of the first sheet is at least 2.5 times that of the second sheet and 3 times that of the third sheet.

[0045] (3) The first sheet, the second sheet and the third sheet are stacked in the same width direction in increasing or decreasing thickness, and are fed into a pair of metal rollers along the length direction and rolled to a thickness range of 0.05 to 1 mm, preferably 0.15 to 0.6 mm, to form a laminated body, such as Figure 1 shown.

[0046] (4) The laminate is dried at 200-250°C, and then expanded along the speed direction at 250-350°C at a stretching rate of 20% / s to 3000% / s, preferably 50% / s to 2000% / s, and an expansion ratio of 50% to 900%, preferably 80% to 800%, to form a uniaxially stretched product.

[0047] (5) The uniaxially stretched product is stretched at a temperature of 200 to 400° C. at a stretching rate of 5% / s to 500% / s, preferably at a stretching rate of 20% / s to 300% / s, and at a ratio of 300% to 3000%, preferably at a ratio of 500% to 2500%, in a direction perpendicular to the speed to finally form a polytetrafluoroethylene (PTFE) membrane material having a gradient pore structure.

[0048] The cross section of the membrane material has a gradient pore structure. The polytetrafluoroethylene (PTFE) membrane material has two upper and lower outer surfaces, which are a first porous outer surface and a second porous outer surface, respectively. The two surfaces have fibers and nodes with different microstructures.

[0049] The first porous outer surface has an island-like microstructure constructed by a plurality of interconnected smaller nodes. The smaller nodes are circular structures with an average diameter of 0.30 to 1.50 μm. The smaller nodes are connected by a plurality of thick and short microfibers, the average length of the thick and short microfibers is in the range of 0.2 to 2.5 μm, the average diameter is in the range of 0.05 to 0.2 μm, and the aspect ratio is 2 to 20.

[0050] The second porous outer surface has an H-shaped ladder-like microstructure constructed by a plurality of interconnected larger nodes. The larger nodes are long elliptical structures with an average length of 0.5 to 10 μm and an average width of 0.5 to 2 μm. The larger nodes are connected by a plurality of slender microfibers, the average length of the slender microfibers is in the range of 1 to 10 μm, the average diameter is in the range of 5 to 200 nm, and the aspect ratio is 10 to 200.

[0051] Testing method for polytetrafluoroethylene membrane material

[0052] 1. Thickness measurement

[0053] The film thickness was measured by placing the film or sheet between the probe and anvil of a Mitutoyo Model 7327 Thickness Micrometer. The average of three measurements was used.

[0054] 2. Bubble point measurement

[0055] The bubble point and mean flow pore size were measured using a capillary flow porometer (Porolux pore size analyzer) (model Porolux 500, Porometer NV, Belgium) according to the general guidelines of ASTM F316-03. The sample membrane was placed in the sample chamber and wetted with a test liquid with a surface tension of 16 dynes / cm. The values ​​​​expressed for bubble point and mean flow pore size are the average of two measurements.

[0056] 3. Scanning electron microscope images

[0057] SEM images were generated using a cold field emission scanning electron microscope (Hitachi Regulus 8100).

[0058] 4. Node and fiber size measurement

[0059] SolidWorks 2014 software (Dassault Systemes, France) was used to perform proportional measurements on the SEM photos, and the measurement results were converted into the actual sizes of nodes and fibers using the scale of the SEM photos.

[0060] The present invention is described in detail with reference to the following examples, but the present invention is not limited by these examples.

[0061] Example 1

[0062] Daikin F-106 polytetrafluoroethylene dispersion resin was uniformly mixed with 18.3% by weight of isoparaffin (ExxonMobil ISOPAR M) and placed in a constant temperature oven at 25°C for 18 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through a T-die at a compression ratio of 195 to obtain a continuous first sheet with a rectangular cross section and a thickness of 0.4 mm.

[0063] CD-126E polytetrafluoroethylene dispersion resin of Asahi Glass was uniformly mixed with 25.6% by weight of isoparaffin (ExxonMobil ISOPAR K), and placed in a constant temperature oven at 25°C for 18 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through T-shaped dies of different specifications at a compression ratio of 49 to obtain a continuous second sheet with a rectangular cross section and a thickness of 0.9 mm, and a continuous third sheet with a rectangular cross section and a thickness of 1.2 mm was extruded at a compression ratio of 37.

[0064] Three sheets of different specifications are stacked in the same width direction in increasing or decreasing thickness, and enter a pair of metal rollers along the length direction and are rolled to 0.3mm in the thickness direction to form a laminate. The dried laminate with the auxiliary oil removed is longitudinally stretched by a longitudinal stretching mechanism, the stretching roller temperature is 300°C, the stretching rate is 117% / s, and the stretching expansion ratio is 230%. The unidirectionally stretched product (base tape) after longitudinal stretching is transversely stretched by a transverse expander, the stretching temperature is 250°C, the stretching rate is 22% / s, and the stretching expansion ratio is 2000%, and finally heat-set to form a film.

[0065] As described above, the obtained polytetrafluoroethylene (PTFE) microporous membrane has a first porous outer surface and a second porous outer surface with different microstructures. Figure 2-3 As shown, Figure 2 This is a scanning electron micrograph (SEM) of the first porous outer surface of the PTFE membrane taken at 2000 times magnification, showing an island-like microstructure constructed by several interconnected smaller nodes; Figure 3 This is a scanning electron micrograph (SEM) of the second porous outer surface of the PTFE membrane taken at 2000 times magnification, showing an H-shaped ladder-like microstructure constructed by several larger nodes connected to each other.

[0066] Using Solidworks2014 software Figure 2 The nodes are measured in proportion, and the node sizes are shown in Table 1 below.

[0067] Table 1 Node size of the first porous outer surface

[0068]

[0069]

[0070] Using Solidworks2014 software Figure 2 The fibers were measured in equal proportions and the fiber sizes are shown in Table 2 below.

[0071] Table 2 Fiber size of the first porous outer surface

[0072]

[0073] Using Solidworks2014 software Figure 3 The nodes are measured in proportion and the node sizes are shown in Table 3 below.

[0074] Table 3 Node size of the second porous outer surface

[0075]

[0076] Using Solidworks2014 software Figure 3 The fibers were measured in equal proportions and the fiber sizes are shown in Table 4 below.

[0077] Table 4 Fiber size of the second porous outer surface

[0078]

[0079]

[0080] The bubble point was determined by running two test conditions using a capillary flow porometer. In the first test, the first porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh; in the second test, the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh, and the bubble points were determined to be 1.97 bar and 1.62 bar, respectively.

[0081] Example 2

[0082] Daikin F-106 polytetrafluoroethylene dispersion resin was uniformly mixed with 19.5% by weight of isoparaffin (ExxonMobil ISOPAR M) and placed in a constant temperature oven at 25°C for 20 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through a T-die at a compression ratio of 195 to obtain a continuous first sheet with a rectangular cross section and a thickness of 0.4 mm.

[0083] CD-126E polytetrafluoroethylene dispersion resin of Asahi Glass was uniformly mixed with 23.5% by weight of isoparaffin (ExxonMobil ISOPAR K), and placed in a constant temperature oven at 25°C for 20 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through T-shaped dies of different specifications at a compression ratio of 56 to obtain a continuous second sheet with a rectangular cross section and a thickness of 0.8 mm, and a continuous third sheet with a rectangular cross section and a thickness of 1.0 mm was extruded at a compression ratio of 45.

[0084] The sheets of three different specifications are stacked in the same width direction in increasing or decreasing thickness, and enter a pair of metal rollers in the length direction and are rolled to 0.28mm in the thickness direction to form a laminate. The dried laminate with the auxiliary oil removed is longitudinally stretched by a longitudinal stretching mechanism, the stretching roller temperature is 300°C, the stretching rate is 150% / s, and the stretching expansion ratio is 250%. The unidirectionally stretched product (base tape) after longitudinal stretching is transversely stretched by a transverse expander, the stretching temperature is 250°C, the stretching rate is 22% / s, and the stretching expansion ratio is 2000%, and finally heat-set to form a film.

[0085] As described above, the obtained polytetrafluoroethylene membrane has a first porous outer surface and a second porous outer surface with different microstructures, such as Figure 4-5 As shown, Figure 4 This is a scanning electron micrograph (SEM) of the first porous outer surface of a polytetrafluoroethylene (PTFE) membrane taken at 2000 times magnification, showing an island-like microstructure constructed by several interconnected smaller nodes; Figure 5 This is a scanning electron micrograph (SEM) of the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane, taken at 2000 times magnification, showing an H-shaped ladder-like microstructure constructed by several larger nodes connected to each other.

[0086] Using Solidworks2014 software Figure 4 The nodes are measured in proportion and the node sizes are shown in Table 5 below.

[0087] Table 5 Node size of the first porous outer surface

[0088]

[0089] Using Solidworks2014 software Figure 4 The fibers were measured in equal proportions and the fiber sizes are shown in Table 6 below.

[0090] Table 6 Fiber size of the first porous outer surface

[0091]

[0092] Using Solidworks2014 software Figure 5 The nodes are measured in proportion and the node sizes are shown in Table 7 below.

[0093] Table 7 Node size of the second porous outer surface

[0094]

[0095]

[0096] Using Solidworks2014 software Figure 5 The fibers were measured in equal proportions and the fiber sizes are shown in Table 8 below.

[0097] Table 8 Fiber size of the second porous outer surface

[0098]

[0099] The bubble point was determined by running two test conditions using a capillary flow porometer. In the first test, the first porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh; in the second test, the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh, and the bubble points were determined to be 1.78 bar and 1.53 bar, respectively.

[0100] Example 3

[0101] Daikin F-106 polytetrafluoroethylene (PTFE) dispersion resin was uniformly mixed with 21.3% by weight of isoparaffin (ExxonMobil ISOPAR M) and placed in a constant temperature oven at 25° C. for 22 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through a T-die at a compression ratio of 195 to obtain a continuous first sheet with a rectangular cross section and a thickness of 0.4 mm.

[0102] CD-126E polytetrafluoroethylene dispersion resin of Asahi Glass was uniformly mixed with 25.5% by weight of isoparaffin (ExxonMobil ISOPAR K), and placed in a constant temperature oven at 25°C for 22 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through T-shaped dies of different specifications at a compression ratio of 56 to obtain a continuous second sheet with a rectangular cross section and a thickness of 0.8 mm, and a continuous third sheet with a rectangular cross section and a thickness of 1.2 mm was extruded at a compression ratio of 37.

[0103] Three sheets of different specifications are stacked in the same width direction in increasing or decreasing thickness, and enter a pair of metal rollers along the length direction and are rolled to 0.32mm in the thickness direction to form a laminate. The dried laminate with the auxiliary oil removed is longitudinally stretched by a longitudinal stretching mechanism, the stretching roller temperature is 300°C, the stretching rate is 66.7% / s, and the stretching expansion ratio is 200%. The unidirectionally stretched product (base tape) after longitudinal stretching is transversely stretched by a transverse expander, the stretching temperature is 250°C, the stretching rate is 22% / s, and the stretching expansion ratio is 2000%, and finally heat-set to form a film.

[0104] As described above, the obtained polytetrafluoroethylene (PTFE) membrane has a first porous outer surface and a second porous outer surface with different microstructures, such as the attached Figure 6-7 As shown, Figure 6 This is a scanning electron micrograph (SEM) of the first porous outer surface of a polytetrafluoroethylene (PTFE) membrane taken at 2000 times magnification, showing an island-like microstructure constructed by several interconnected smaller nodes; Figure 7 This is a scanning electron micrograph (SEM) of the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane, taken at 2000 times magnification, showing an H-shaped ladder-like microstructure constructed by several larger nodes connected to each other.

[0105] Using Solidworks2014 software Figure 6 The nodes are measured in proportion and the node sizes are shown in Table 9 below.

[0106] Table 9 Node size of the first porous outer surface

[0107]

[0108] Using Solidworks2014 software Figure 6 The fibers were measured in equal proportions and the fiber sizes are shown in Table 10 below.

[0109] Table 10 Fiber size of the first porous outer surface

[0110]

[0111]

[0112] Using Solidworks2014 software Figure 7 The nodes are measured in proportion and the node sizes are shown in Table 11 below.

[0113] Table 11 Node size of the second porous outer surface

[0114]

[0115] Using Solidworks2014 software Figure 7 The fibers were measured in equal proportions and the fiber sizes are shown in Table 12 below.

[0116] Table 12 Fiber size of the second porous outer surface

[0117]

[0118] The bubble point was determined by running two test conditions using a capillary flow porometer. In the first test, the first porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh; in the second test, the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh, and the bubble points were determined to be 2.16 bar and 1.51 bar, respectively.

[0119] Example 4

[0120] A polytetrafluoroethylene dispersion resin was uniformly mixed with 19.5% by weight of isoparaffin, and then placed in a constant temperature oven at 25° C. for 20 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through a T-die at a compression ratio of 190 to obtain a continuous first sheet with a rectangular cross section and a thickness of 0.5 mm.

[0121] A polytetrafluoroethylene dispersion resin was uniformly mixed with 23.5% by weight of isoparaffin, and then placed in a constant temperature oven at 25°C for 20 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through T-shaped dies of different specifications at a compression ratio of 56 to obtain a continuous second sheet with a rectangular cross section and a thickness of 0.8 mm, and a continuous third sheet with a rectangular cross section and a thickness of 1.0 mm was extruded at a compression ratio of 45.

[0122] The three specifications of sheets are stacked in the same width direction in increasing or decreasing thickness, and enter a pair of metal rollers along the length direction and are rolled to 0.28mm in the thickness direction to form a laminate. The dried laminate with the auxiliary oil removed is longitudinally stretched by a longitudinal stretching mechanism, the stretching roller temperature is 300°C, the stretching rate is 150% / s, and the stretching expansion ratio is 250%. The unidirectionally stretched product (base tape) after longitudinal stretching is transversely stretched by a transverse expander, the stretching temperature is 250°C, the stretching rate is 22% / s, and the stretching expansion ratio is 2000%, and finally heat-set to form a film.

[0123] As described above, the obtained polytetrafluoroethylene (PTFE) membrane has a first porous outer surface and a second porous outer surface with different microstructures, such as the attached Figure 8-9 As shown, Figure 8This is a scanning electron micrograph (SEM) of the first porous outer surface of a polytetrafluoroethylene (PTFE) membrane taken at 2000 times magnification, showing an island-like microstructure constructed by several interconnected smaller nodes; Fig. 9 This is a scanning electron micrograph (SEM) of the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane, taken at 2000 times magnification, showing an H-shaped ladder-like microstructure constructed by several larger nodes connected to each other.

[0124] The bubble point was determined by running two test conditions using a capillary flow porometer. In the first test, the first porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh, and in the second test, the second porous outer surface of the polytetrafluoroethylene (PTFE) membrane faced the metal mesh, and the bubble points were determined to be 2.89 bar and 1.61 bar, respectively.

[0125] Example 5

[0126] Daikin F-106 polytetrafluoroethylene dispersion resin was uniformly mixed with 19.5% by weight of isoparaffin, and then placed in a constant temperature oven at 25°C for 18 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through a T-die at a compression ratio of 190 to obtain a continuous first sheet with a rectangular cross section and a thickness of 0.5 mm.

[0127] CD-126E polytetrafluoroethylene dispersion resin from Asahi Glass was uniformly mixed with 21.6% by weight of isoparaffin, and then placed in a constant temperature oven at 25°C for 18 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through T-shaped dies of different specifications at a compression ratio of 49 to obtain a continuous second sheet with a rectangular cross section and a thickness of 0.9 mm, and a continuous third sheet with a rectangular cross section and a thickness of 1.2 mm was extruded at a compression ratio of 37.

[0128] The three specifications of sheets are stacked in the same width direction in increasing or decreasing thickness, and enter a pair of metal rollers along the length direction and are rolled to 0.32mm in the thickness direction to form a laminate. The dried laminate with the auxiliary oil removed is longitudinally stretched by a longitudinal stretching mechanism, the stretching roller temperature is 300°C, the stretching rate is 66.7% / s, and the stretching expansion ratio is 200%. The unidirectionally stretched product (base tape) after longitudinal stretching is transversely stretched by a transverse expander, the stretching temperature is 250°C, the stretching rate is 22% / s, and the stretching expansion ratio is 2000%, and finally heat-set to form a film.

[0129] As described above, the obtained PTFE microporous membrane has a first porous outer surface and a second porous outer surface with different microstructures. Figure 10-11 As shown, Fig.10This is a scanning electron micrograph (SEM) of the first porous outer surface of the PTFE membrane taken at 2000 times magnification, showing an island-like microstructure constructed by several interconnected smaller nodes; Fig.11 This is a scanning electron micrograph (SEM) of the second porous outer surface of the PTFE membrane taken at 2000 times magnification, showing an H-shaped ladder-like microstructure constructed by several larger nodes connected to each other.

[0130] The bubble point was determined by running two test conditions using a capillary flow porometer. In the first test, the first porous outer surface of the PTFE membrane faced the metal mesh, and in the second test, the second porous outer surface of the PTFE membrane faced the metal mesh, and the bubble points were determined to be 2.35 bar and 1.77 bar, respectively.

[0131] Example 6

[0132] A polytetrafluoroethylene dispersion resin was uniformly mixed with 21.3% by weight of isoparaffin (ExxonMobil ISOPAR M) and placed in a constant temperature oven at 30° C. for 15 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through a T-die at a compression ratio of 190 to obtain a continuous first sheet with a rectangular cross section and a thickness of 0.5 mm.

[0133] A polytetrafluoroethylene dispersion resin was uniformly mixed with 26.2% by weight of isoparaffin (ExxonMobil ISOPAR K) and placed in a constant temperature oven at 30°C for 15 hours. The PTFE resin mixture was pressed into a cylindrical preform, and then the cylindrical preform was extruded through T-shaped dies of different specifications at a compression ratio of 56 to obtain a continuous second sheet with a rectangular cross section and a thickness of 0.8 mm, and a continuous third sheet with a rectangular cross section and a thickness of 1.2 mm was extruded at a compression ratio of 37.

[0134] The three specifications of sheets are stacked in the same width direction in increasing or decreasing thickness, and enter a pair of metal rollers along the length direction and are rolled to 0.3mm in the thickness direction to form a laminate. The dried laminate with the auxiliary oil removed is longitudinally stretched by a longitudinal stretching mechanism, the stretching roller temperature is 300°C, the stretching rate is 117% / s, and the stretching expansion ratio is 230%. The unidirectionally stretched product (base tape) after longitudinal stretching is transversely stretched by a transverse expander, the stretching temperature is 250°C, the stretching rate is 22% / s, and the stretching expansion ratio is 2000%, and finally heat-set to form a film.

[0135] As described above, the obtained PTFE microporous membrane has a first porous outer surface and a second porous outer surface with different microstructures. Figure 12-13 As shown, Fig.12This is a scanning electron micrograph (SEM) of the first porous outer surface of the PTFE membrane taken at 2000 times magnification, showing an island-like microstructure constructed by several interconnected smaller nodes; Fig.13 This is a scanning electron micrograph (SEM) of the second porous outer surface of the PTFE membrane taken at 2000 times magnification, showing an H-shaped ladder-like microstructure constructed by several larger nodes connected to each other.

[0136] The bubble point was determined by running two test conditions using a capillary flow porometer. In the first test, the first porous outer surface of the PTFE membrane faced the metal mesh, and in the second test, the second porous outer surface of the PTFE membrane faced the metal mesh, and the bubble points were determined to be 2.12 bar and 1.68 bar, respectively.

[0137] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

[0138] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A polytetrafluoroethylene membrane with a gradient pore structure, characterized in that: The cross-section of the polytetrafluoroethylene membrane has a gradient pore structure, and the first porous outer surface and the second porous outer surface of the polytetrafluoroethylene membrane have fibers and nodes with different microstructures; the first porous outer surface has an island-like microstructure constructed by a plurality of interconnected smaller nodes, and the second porous outer surface has an H-shaped ladder-like microstructure constructed by a plurality of interconnected larger nodes.

2. The polytetrafluoroethylene membrane with a gradient pore structure according to claim 1, characterized in that: The smaller nodes are circular in structure, with an average diameter of 0.30 to 1.50 μm.

3. The polytetrafluoroethylene membrane with a gradient pore structure according to claim 2, characterized in that: The smaller nodes are formed by connecting a number of thick and short microfibers. The average length of the thick and short microfibers is in the range of 0.2 to 2.5 μm, the average diameter is in the range of 0.05 to 0.2 μm, and the aspect ratio is 2 to 20.

4. The polytetrafluoroethylene membrane with a gradient pore structure according to claim 1, characterized in that: The larger nodes are long oval structures with an average length of 0.5 to 10 μm and an average width of 0.5 to 2 μm.

5. The polytetrafluoroethylene membrane with a gradient pore structure according to claim 4, characterized in that: The larger nodes are formed by connecting a number of thin and long microfibers, the average length of the thin and long microfibers is in the range of 1 to 10 μm, the average diameter is in the range of 5 to 200 nm, and the aspect ratio is 10 to 200.

6. A method for preparing a polytetrafluoroethylene membrane having a gradient pore structure as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) First, isoparaffin and PTFE dispersed resin are uniformly mixed to obtain a PTFE resin mixture, and then the PTFE resin mixture is pressed into a cylindrical preform; (2) using an extruder to extrude the cylindrical preform into three continuous strips of equal width and different thicknesses with rectangular cross-sections through T-shaped extrusion dies of different specifications, namely, a first sheet, a second sheet, and a third sheet; (3) The first sheet, the second sheet, and the third sheet are stacked in the same width direction in increasing or decreasing thickness, and are fed into a pair of metal rollers in the length direction and rolled in the thickness direction to a range of 0.05 to 1 mm to form a laminate; (4) drying the laminate at 200 to 250° C., and then expanding the laminate in a speed direction at 250 to 350° C. at a stretching rate of 20% / s to 3000% / s and an expansion ratio of 50% to 900% to form a uniaxially stretched product; (5) Expanding the uniaxially stretched product in a direction perpendicular to the speed at a temperature of 200 to 400° C., at a stretching rate of 5% / s to 500% / s, and at a ratio of 300% to 3000%, to finally form a PTFE membrane material with a gradient pore structure.

7. The method for preparing a polytetrafluoroethylene membrane having a gradient pore structure according to claim 6, characterized in that: In step (1), isoparaffin and PTFE dispersed resin are uniformly mixed in a weight ratio of 15 to 30% to obtain a PTFE resin mixture, and the mixture is dried at a temperature not less than 20° C. for more than 12 hours, and the PTFE resin mixture is pressed into a cylindrical preform.

8. The method for preparing a polytetrafluoroethylene membrane having a gradient pore structure according to claim 7, characterized in that: In step (2), the cylindrical preform is extruded into three kinds of equal-width continuous strip sheets of different thicknesses with rectangular cross-sections through T-shaped extrusion dies of different specifications at a compression ratio of 20 to 500, namely a first sheet, a second sheet and a third sheet, wherein: the thickness of the second sheet is at least 1.2 times the thickness of the first sheet, the thickness of the third sheet is at least 1.2 times the thickness of the second sheet, and the compression ratio of the first sheet is at least 2.5 times that of the second sheet and 3 times that of the third sheet.

9. The method for preparing a polytetrafluoroethylene membrane having a gradient pore structure according to claim 8, characterized in that: In step (4), the laminate is expanded along the speed direction at a stretching rate of 50% / sec to 2000% / sec and an expansion ratio of 80% to 800% to form a uniaxially stretched product.

10. The method for preparing a polytetrafluoroethylene membrane having a gradient pore structure according to claim 9, characterized in that: In step (5), the film is expanded in a direction perpendicular to the speed at a stretching rate of 20% / sec to 300% / sec and a ratio of 500% to 2500%, thereby finally forming a PTFE membrane material with a gradient pore structure.

Citation Information

Patent Citations

  • Asymmetric polytetrafluoroethylene composite having a macro-textured surface and method for making the same

    CN107810047A

  • Process for producing porous products

    US3953566A

  • Asymmetric porous film materials and process for producing same

    US4248924A